Anti-PL-12 Antibody-positive Interstitial Pneumonia Diagnosed During Treatment for Rheumatoid Arthritis - Sano, Go; Homma, Sakae; Shibuya, Kazutoshi; Uekusa, Toshimasa; Shimizu, Hiroshige; Sugino, Keishi (The Journal of the Japan Society for Respiratory Endoscopy, 2022)
Backgroud. The onset of interstitial pneumonia during treatment of rheumatoid arthritis (RA) rarely leads to the diagnosis of anti-aminoacyl tRNA synthetase (ARS) syndrome. Case. A 66-year-old man was admitted to our hospital complaining of a 1-month history of persistent cough and dyspnea on exertion with the onset of interstitial pneumonia during treatment, such as sodium aurothiomalate for RA. Chest high-resolution computed tomography (HRCT) revealed diffuse reticular lesions, interlobular septal thickening, and traction bronchiectasis, admixed with consolidation predominantly in the bilateral lower lobes. The histopathological findings of video-assisted thoracic surgery (VATS) specimens showed fibro-cellular non-specific interstitial pneumonia. Consequently, we diagnosed him with anti-ARS syndrome due to positive serum findings for anti-PL-12 antibody. Conclusion. Anti-ARS antibodies should be measured in patients with suspected connective tissue disease-interstitial lung disease showing the above findings on HRCT.